Penerapan Cost Leadership PT Angkasa Pura I dalam Mengurangi Dampak Covid-19 (Saat Pandemi dan Pasca Pandemi Covid-19) - Azana, Syaifanni; Muliawati, Elsa Alifia; Larasati, Annisa; Wibowo, Saffanah Zerlina; Edwina, Nabilah Putri; Nabila, Nisa Uzzahron; Irawan, Ferry (Akuntansiku, 2024)
Companies had huge challenges when the Covid-19 pandemic hit the world, including airport management companies. To maintain the company's existence amidst many limitations, PT Angkasa Pura I is considering several alternative strategies that it feels are appropriate. This research aims to investigate the condition of companies during the pandemic and the implementation of appropriate cost strategies to maintain business continuity. By using a qualitative approach and case study approach, this research produced several important findings. First, the company focuses on cost efficiency by optimizing the use of technology. Second, the company succeeded in reducing operating expenses in 2020 until 2022. Third, even though costs can be reduced, service to customers can still be maintained well.